Rapid and label-free identification of single foodborne pathogens using microfluidic pore sensors - Yang, Tao; Luo, Zisheng; Wu, Ricardo A.; Li, Li; Xu, Yanqun; Ding, Tian; Lin, Xingyu (Frontiers in Nutrition, 2022)
Foodborne pathogenic microorganisms have become major threats that endanger human life and health. The current technology cannot perform rapid screening of foodborne pathogenic bacteria, and fail to timely control of food safety risks. Here, we develop a novel microfluidic sensor for real-time and label-free bacteria classification at single-cell level. Concretely, a low-aspect-ratio SiN micropore with PDMS coating was fabricated, which could significantly reduce the noise of the sensing system, and makes the microfluidic pore sensor sensitive for bacteria discrimination. The prepared SiN micropore equipped with high temporal-spatial resolution was applied to observe bacterial translocation “events” and the current pulse signals could be obtained, which depend on the size, charge, and morphology of the target bacteria. According to the variation of current pulse signals produced by different bacteria across the micropore, three common foodborne pathogens such as Salmonella enteric, Listeria monocytogenes, and Escherichia coli were identified. Due to convenience, rapidity and accuracy, the label-free method we report here has great potential for identification of diverse foodborne microorganisms at single-cell sensitivity.